2020
DOI: 10.7739/jkafn.2020.27.1.64
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Breast Cancer Patients’ Commitment to a Plan for Exercise based on Health Beliefs

Abstract: Purpose: The purpose of this study was to identify the factors relating to commitment to a plan for exercise in the breast cancer patient following a mastectomy and to examine the relationship between these factors.Methods: This study was a correlational research and the participants were 152 patients with breast cancer. Data were collected using a structured questionnaire from June to October, 2015.Results: The final regression model showed that income, experience of exercise and current exercise were signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The main reasons for exclusion were, no quantitative data, unsuitable study outcomes (no predictive factors of adherence), unsuitable study design (review or protocol) or it concerned a PhD-thesis of which no full text article was available or could not be obtained through the author (Figure 1 and Supplementary Appendix S4). We included the remaining 57 studies in this systematic review, of which two studies were translated from Korean into English (29,30). No additional studies were identified through handsearching or a search in the grey literature.…”
Section: Included Studiesmentioning
confidence: 99%
“…The main reasons for exclusion were, no quantitative data, unsuitable study outcomes (no predictive factors of adherence), unsuitable study design (review or protocol) or it concerned a PhD-thesis of which no full text article was available or could not be obtained through the author (Figure 1 and Supplementary Appendix S4). We included the remaining 57 studies in this systematic review, of which two studies were translated from Korean into English (29,30). No additional studies were identified through handsearching or a search in the grey literature.…”
Section: Included Studiesmentioning
confidence: 99%
“…Although 74% of BCSs wish to work, only 54% successfully return to work, 37 indicating the potential for financial burden 38 . Moreover, BCSs with a higher monthly income showed quality exercise plans 39 . In contrast, low-income female heads of households 40 did not have the financial or psychological leeway to care for their health or leisure time.…”
Section: Discussionmentioning
confidence: 99%
“…38 Moreover, BCSs with a higher monthly income showed quality exercise plans. 39 In contrast, low-income female heads of households 40 did not have the financial or psychological leeway to care for their health or leisure time. These individuals were also deprived of cancer-related information.…”
Section: Jun and Leementioning
confidence: 99%